2018
DOI: 10.1111/cid.12643
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soft tissue grafting, orofacial implant position, and angulation on facial hard and soft tissue thickness at immediately inserted and provisionalized implants in the anterior maxilla

Abstract: The results indicate that an initial severe hard tissue defect allows for significant bone regeneration. The facial soft tissue thickness is primarily influenced by the gingival biotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 30 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…The reasons for exclusion can be found in Table 1. Thus, 8 articles fully met the selection criteria for qualitative analysis (Bianchi & Sanfilippo, 2004; Cornelini et al, 2008; Migliorati et al, 2015; van Nimwegen et al, 2018; Noelken et al, 2018; Rungcharassaeng et al, 2012; Yoshino et al, 2014; Zuiderveld et al, 2018). Of those, 5 articles were included for quantitative analysis (Bianchi & Sanfilippo, 2004; Migliorati et al, 2015; van Nimwegen et al, 2018; Yoshino et al, 2014; Zuiderveld et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for exclusion can be found in Table 1. Thus, 8 articles fully met the selection criteria for qualitative analysis (Bianchi & Sanfilippo, 2004; Cornelini et al, 2008; Migliorati et al, 2015; van Nimwegen et al, 2018; Noelken et al, 2018; Rungcharassaeng et al, 2012; Yoshino et al, 2014; Zuiderveld et al, 2018). Of those, 5 articles were included for quantitative analysis (Bianchi & Sanfilippo, 2004; Migliorati et al, 2015; van Nimwegen et al, 2018; Yoshino et al, 2014; Zuiderveld et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies are reported in Table 2. Five articles were RCTs (Bianchi & Sanfilippo, 2004; Migliorati et al, 2015; van Nimwegen et al, 2018; Yoshino et al, 2014; Zuiderveld et al, 2018) and 3 were NRSs (Cornelini et al, 2008; Noelken et al, 2018; Rungcharassaeng et al, 2012). The qualitative analysis comprised data of 409 single immediate implants installed in 388 patients with a mean age ranging from 43 to 53 years (IIP + CTG: 246 implants in 236 patients; IIP: 163 implants in 152 patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review reported the buccal gingival thickness of the natural teeth with an average of 0.63-1.79 mm (Zweers, Thomas, Slot, Weisgold, & Weijden, 2014). In addition, Noelken have used ultrasonic device to measure the peri-implant soft tissue thickness on the mid-buccal side, which was 1.72, 1.63, 1.52 and 1.66 mm, respectively, at 1/4/6/9 mm apical to the implant shoulder (Noelken, Geier, Kunkel, Jepsen, & Wagner, 2018). These results were basically consistent with the current outcomes.…”
Section: Discussionmentioning
confidence: 99%